Effect of Extraction Method of Loess in Cotton Fabric Dyeing - NAJAFI, HOSSEIN; ASSEFIPOUR, REZA (Asian Journal of Chemistry, 2010)
In this research, cotton samples dyeing with ball-milled loess showed larger increase in dye uptake and the change to more reddish yellow colour than that with the elutriated one. With the increase of ball-milling time, it was decreased to smaller size and changed from multi-layer to ragged spherical or rod-like form. For narrower particle size distribution and smaller particle size, K/S value of cotton fabric was increased and the colour was changed to more reddish yellow. SEM analysis confirmed that the loess particle did not penetrate inside the fiber but adhered the surface of cotton fiber.